The Effects of U-Shaped Side Groove on the Fracture Properties of Aluminium Alloy 6061 using Finite Element Method Analysis - Mohd Radzi, Muhammad Haiqal; harimon, mohd azhar (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Automotive industry engineering responsible to produce the automotive vehicles with a safe used for the people. They usually used the aluminium alloy to produce the good product regarding to the properties that suitable for the automotive making. The material of Aluminium Alloy 6061 used in this study to study about the fracture properties of the alloy. One parameter have been applied in this study which is the effect of the side groove depth on the aluminium alloy specimen. In this research study, Single Edge Notch Bending test with different side groove depth ratio was conducted through a simulation by using the Abaqus Software in order to identify the absorb energy, displacement and also the maximum principal stress and strain on the specimen. Various side groove depth on the specimen which is 2mm, 3mm and 4mm were conducted through the SENB simulation. It show that the absorb energy value is decreasing when the side groove depth is deeper. The value of the displacement of fracture show that the displacement is increasing when the side groove depth is deeper. In conclusion, the Aluminium Alloy 6061 tend to become less on ductility behaviour when the side groove depth is deeper due to the result obtained.